KHARAKTERISTIK MUFFIN DARI TEPUNG UBIJALAR UNGU KAYA PATI RESISTEN (The characteristics of muffin from resistant starch- rich purple sweet potato flour) - Siti Nurdjanah; neti Yuliana; Ahmad Sapta Zuidar; Ira Ervinda Naim (Majalah TEGI, 2017)
Resistant starch- rich purple sweet potato flour can be used as wheat substitute in muffin production, partly  because of its potential health benefit.  The aim of this research was to find proper  ratio between wheat flour and purple sweet potato flour to obtained muffins  with the best sensory properties and to elucidate  the chemical contents and caloric value of the muffins.  This research was arranged in a complete randomized block design with four replications.  The  single factor treatment was consisted of 6 levels of ratios between purple sweet potato flour and wheat flour :  U1 (15:85), U2 (30:70), U3 (45:55), U4 (60:40), U5 (75:25), and U6 (90:10).  The parameters observed were sensory characteristic, followed by proximate analysis, anthocyanin content, antioxidant capacity, and  caloric value.  The results showed that the best ratio between sweet potato flour and wheat flour  for producing muffin was found in the ratio of  This muffin  contains 35,92 % water, 1,79 % ash , 23,64 % fat, 31,11 % carbohydrate, 7.54 % protein , 45 ±16 mg/100 g total anthocyanin, and  IC50 value of 249,34 μg/mL, and caloric value  of 3,087 kal/g.